If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 18 = 7 Reorder the terms: 18 + n = 7 Solving 18 + n = 7 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + n = 7 + -18 Combine like terms: 18 + -18 = 0 0 + n = 7 + -18 n = 7 + -18 Combine like terms: 7 + -18 = -11 n = -11 Simplifying n = -11
| 10x-x-2x-x= | | 11x+25=7x+5 | | -3x-9=2x+7 | | -7r-3+2r= | | 3(2x+2)-4=5(x+1) | | .06+0.08(100-x)=4.2 | | 11x+13y=90 | | x^2-112=20x | | -8x-4x= | | -2(2x-4)=3(-12x+24) | | 2(6x+9)= | | 8x+20+16x-8=180 | | x^2+112=20 | | 4(-2)*2=8(-2)+3(-2)+6 | | 8+15i=2ni+3ni | | -12r=52+(-4) | | x-13=-34 | | 2x+5-6(x+1)=7x-5 | | 32x+6=12x-4 | | x-3*x=40 | | 2(x+1)=6+3x | | 8x-x=-49 | | -24x+x= | | 5(-4+2y)-3y=1 | | (-16)=(-19)-w | | 14q=-21 | | 2-5a-b=4 | | (x+12)*8=4*x | | -5c=-35 | | -4(n-1)=11 | | 720x-2157=x | | 9(n-3)+13=40 |